Increasing public awareness through education and the implementation of routine blood donations - Suprapto Suprapto; Darmi Arda; Maria Kurni Menga; Hartaty Hartaty; Abdul Halis; Bayu Adji (Jurnal Pengabdian Masyarakat Edukasi Indonesia, 2024)
This community service program aims to increase public awareness and participation in blood donation activities through education and the regular implementation of blood donation. Adequate blood availability in blood transfusion units is critical to saving lives, but community participation in blood donation is still low in some areas. Through this activity, counselling was carried out to the community about the benefits of blood donation, health requirements, and the importance of blood donation continuity for medical emergency needs. This program collaborates with the Indonesia Red Cross (PMI) and local health facilities to organize routine blood donation activities every three months. It is hoped that with this program, community participation in blood donation will increase significantly, and sustainable awareness about the importance of sharing and helping others through blood donation will be created. The results of this activity were measured through an increase in the number of blood donation participants and an evaluation of community knowledge after counselling was carried out